Development of drug loaded biodegradable polymer composite microparticles - Li, Yan (2011)
Calcium hydroxyapatite (HA) is the main inorganic component of natural bones and widely used as coating material on bone implants due to its osteoconductive characteristic. Other metal ions besides Ca can be introduced into HA through ion exchange or coprecipitation method to form metal ion doped HA (MHA), which has been used as catalyst or absorbent. In this investigation, gadolinium(III) (Gd3+), neodymium(III) (Nd3+), manganese(II) (Mn2+) and iron(III) (Fe3+) substituted HA at different molar ratios (Madded/Caadded = XM, 0.01, 0.05, 0.1 and 0.2) were synthesized using wet chemical method coupled with ion exchange mechanism. Calcium hydroxide Ca(OH)2 and phosphoric acid H3PO4 were used as reactants.